Heavy mental workload increase poor sleep quality in informal garment workers - Merijanti, Lie T; Pusparini, Pusparini; Meiyanti, Meiyanti; Alvina, Alvina; Sudharma, Novia I; Tjahjadi, Muljadi (Universa Medicina, 2019)
Background Sleep is needed by the human body so that the performance of body remains optimal when the body is awake, especially during work. Informal workers often work without clear regulations, with inadequate equipment and poor work environment, and pay little attention to occupational health and safety factors. The existence of large work demands with unclear work system arrangements will certainly result in a mental workload in these workers. The objective of this study was to determine the relationship between mental workload and sleep patterns of workers in the informal garment sector. MethodsA cross-sectional study involving 225 informal garment workers was conducted between December 2018 and May 2019. Data collection included respondentsâ€™ demographics, job characteristics, measurement of mental burden and disturbances in sleep patterns. The sleep pattern used the PSQI (Pittsburgh Sleep Quality Index) instrument and the mental burden used the Rating Scale Mental Effort (RSME). A multiple linear regression analysis was used to analyze the data. ResultsThe mean sleep quality was 5.40 Â± 2.54. Multiple linear regression test found that mental workload correlated significantly with sleep quality of workers (Î²=0.016, p=0.012).ConclusionThis study demonstrated that heavy mental workload decreases the quality of sleep in informal garment workers. A good work system management is required so that workers are assigned that portion of the task that is commensurate with their capacity.